Pengaruh Slow Deep Breathing Terhadap Penurunan Nyeri Punggung Menjelang Persalinan - Nurhayani Nurhayani; Salwa Annisaa; Dian Shofia Reny S (Universitas Muhammadiyah Manado, 2026)
Labor pain begins in the first stage, which includes the latent phase (cervical dilation up to 3 cm) and the active phase (cervical dilation from 4 cm to 10 cm). The active phase sees an increase in the intensity and frequency of contractions, leading to peak pain. Research on 2,700 delivering mothers found that 15% experienced mild pain, 35% moderate pain, 30% severe pain, and 20% very severe pain. To reduce maternal mortality (AKI), minimizing labor pain is crucial. Labor pain can be controlled through pharmacological and non-pharmacological methods. Non-pharmacological methods include counter pressure, hypnobirthing, endorphin massage, effleurage massage, relaxation techniques, warm compresses, Mozart music, murottal therapy, acupressure, and aromatherapy. Distraction and pain management techniques are vital for healthcare providers to help reduce pain, especially during the first stage of labor. One effective method is deep breathing relaxation, where regulating the breathing pattern can reduce pain caused by cervical dilation. Slow deep breathing, a conscious relaxation technique, has several benefits, such as reducing stress and anxiety, improving focus, lowering blood pressure, enhancing sleep quality, and improving digestion. Objective: To determine the effect of slow deep breathing on labor pain reduction. Results: Wilcoxon statistical test showed a significance value of ρ = 0.023 (ρ<0.05), indicating a significant difference in labor pain levels before and after applying slow deep breathing. Conclusion: Slow deep breathing reduces labor pain levels.